(untitled) (Bulletin KNOB, 1990)
In 1987 the country seat Heemstede (1645) especially famous for the grand formal layout of the gardens and the beautiful interiors by Daniël Marot (1680-’85) has been destroyed by fire. The dining-room, staircase, cabinet and hall however could be saved. The hall is the only room which preserved its Renaissance character. The floor-tiles form a diagonal chessboard pattern. The two recesses in the middle of the white stucco walls contain beautifully painted hunting scenes. The room possesses refined Renaissance decoration such as the wooden consoles with acanthus leafs supporting the ceiling and channelled cornices above the doors. The dark green paint has been introduced by prof. Vogelsangh at the restoration (1919). The pentagonal cabinet dates from the time of one of the first owners Diderick van Velthuysen (1680-’85). Floor and walls are lined with oak panels and wonderful marquetry, which reminds of English interiors from the period ’William and Mary’. Between the tie-beams of the ceiling putti with garlands are visible. The dining room has been enlarged by making a passage to the cabinet behind. Details resemble those of the cabinet and were also executed under Van Velthuysen. The lowest together forming a wainscot the woodwork has been built up from two panels. The corners contain pilasters with Corinthian capitals. Before Vogelsangh introduced dark green paint and gold-leaf the room was not painted. Unfortunately, the six paintings of the ceiling’s compartments could not be saved. The staircase originates from the rebuilding in 1680-85 by joining the four old tower rooms. These pentagonal rooms have been transformed internally into a round tower with a dome-shaped vault at the level of the third floor. Apart from the simple cornice below this vault and the wooden wainscot on the ground floor the walls are soberly stuccoed. The staircase is the most important element in the whole house. The handrail of wrought iron in Louis XIV style designed by Daniël Marot is one of the rare examples which survived the ravages of time. Exposed to wind and weather staircase and interiors decay in a quick rate. Fast measures are necessary to preserve them for the future.